2017
DOI: 10.1002/ccr3.1182
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia and disseminated histoplasmosis in immunocompetent adults

Abstract: Key Clinical MessageDisseminated histoplasmosis among immunocompetent patients is rare, but may be associated with clinically significant refractory thrombocytopenia. Platelet counts often return to normal levels following antifungal therapy. Therefore, the most important management of this refractory thrombocytopenia is the recognition and treatment of histoplasmosis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Contrary to the aforementioned case, our patient had platelet recuperation 48 hours after the application of the IVIG. The possible mechanisms by which H. capsulatum produces thrombocytopenia have been described: 1) by infiltration of MO affecting platelet production; 2) promoting platelet aggregation; or, 3) inducing ITP [6]. In the MO aspirate of our case, megakaryocytes producers of platelets were reported, and there were no yeasts of H. capsulatum found.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Contrary to the aforementioned case, our patient had platelet recuperation 48 hours after the application of the IVIG. The possible mechanisms by which H. capsulatum produces thrombocytopenia have been described: 1) by infiltration of MO affecting platelet production; 2) promoting platelet aggregation; or, 3) inducing ITP [6]. In the MO aspirate of our case, megakaryocytes producers of platelets were reported, and there were no yeasts of H. capsulatum found.…”
Section: Discussionmentioning
confidence: 54%
“…In 2017, Kutkut I. et al [6], reported a case of severe refractory thrombocytopenia with DH, which, during the course of the illness, required multiple transfusions of platelets and IVIG at a dose of 1g/kg/day for two days without improvement. In this case, after the administration of amphotericin B liposomal at 3 mg/kg/ day for 14 days, followed by itraconazole at 200 mg/day for one year, it favored recuperation and normalization of the platelets, associated with an absence of the urinary antigen of H. capsulatum [6]. Contrary to the aforementioned case, our patient had platelet recuperation 48 hours after the application of the IVIG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Several mechanisms by which H. capsulatum produces thrombocytopenia have been described as (1) by infiltration of bone marrow affecting platelet production; (2) by inducing ITP; or (3) by promoting platelet aggregation. 10 The Infectious Disease Society of America (IDSA) recommends itraconazole therapy for 6-12 weeks for patients with mild/moderate disease. 11 For severe disease, the IDSA recommends liposomal amphotericin B for one to 2 weeks, followed by itraconazole for an additional 12 weeks.…”
Section: Fungal Infection Histoplasmosis Renal Transplant Thrombocyto...mentioning
confidence: 99%